ANALISIS TRANSPARANSI PENGELOLAAN KEUANGAN PEMERINTAH DAERAH BERBASIS WEBSITE SE-JAWA BALI - Welly, Welly; Arifin, M Syahrul; Ghozali, Rosalina; Sabrina, Nina (BALANCE : JURNAL AKUNTANSI DAN BISNIS, 2021)
The study aim was to find out the transparency of regional government financial management based on websites in Java-Bali. This research was a descriptive study, which analyzed the transparency of regional government financial management based on websites in Java and Bali on one variable. The regional financial management is divided into four indicators. The data used was secondary. The technique of collecting the data used was documentation. The data analysis technique used was qualitative analysis. The results showed that the analysis of the transparency of regional government financial management based on websites in Java and Bali had the average in the level of small in 28.37%.